PROCEDURE FOR EVALUATION OF THE SUPPORTING FREQUENCY SIGNAL OF THE SATELLITE COMMUNICATION SYSTEM IN CONTINUOUS MODE - Turovsky , A. L.; Drobik , O. V. (Radio Electronics, Computer Science, Control, 2021)
Context. One of the features of satellite communication systems is the advantageous use in them during the reception of the signal in the continuous mode of phase modulation of signals intended for the transmission of useful information. The use of this type of modulation requires solving the problem of estimating the carrier frequency of the signal. And the estimation itself is reduced to the problem of estimating the frequency of the maximum in the spectrum of a fragment of a sinusoidal signal against the background of additive Gaussian noise. The article considers the process of estimating the carrier frequency of a signal by a satellite communication system in a continuous mode according to the rule of maximum likelihood. Objective. Development of a procedure for estimating the carrier frequency of a signal received by a satellite communication system in a continuous mode according to the maximum likelihood rule. Method. The procedure proposed in the work and the algorithm developed on its basis allows to estimate the carrier frequency according to the rule of maximum likelihood, taking into account the conditions of uncertainty of all signal parameters by the satellite communication system in continuous mode. The results. For the purpose of practical introduction of the specified algorithm in operating schemes of satellite communication, schemes of its hardware realization are offered in work. To illustrate the ratio of the limits of the minimum limiting variance of the carrier frequency estimate, the paper presents dependencies that allow comparing the minimum limiting variance defined by the lower Cramer-Rao boundary and the minimum limiting variance determined taking into account all signal parameters. Conclusions. Analysis of these dependences showed that in real conditions the minimum dispersion of the carrier frequency of the signal according to the rule of maximum likelihood received by the satellite communication system in continuous mode with uncertainty of all signal parameters may differ significantly from the minimum dispersion obtained by applying the lower Kramer-Rao boundary. Prospective research, development and creation of algorithms and techniques aimed at estimating the carrier frequency at the minimum limiting variance in the conditions of uncertainty of all parameters of the received signal should be aimed at the maximum approximation of the minimum limiting variance of the estimated carrier frequency to the lower Cramer-Rao boundary to estimate the carrier frequency under conditions of certainty of other signal parameters.